Progress in neutron techniques: towards improved polymer electrolyte membranes for energy devices. (28th May 2021) - Foglia, Fabrizia; Lyonnard, Sandrine; Sakai, Victoria García; Berrod, Quentin; Zanotti, Jean-Marc; Gebel, Gérard; Clancy, Adam J; McMillan, Paul F
Abstract: Design and implementation of advanced membrane formulations for selective transport of ions and molecular species are critical for creating the next generations of fuel cells and separation devices. It is necessary to understand the detailed transport mechanisms over time- and length-scales relevant to the device operation, both in laboratory models and in working systems under realistic operational conditions. Neutron scattering techniques including quasi-elastic neutron scattering, reflectivity and imaging are implemented at beamline stations at reactor and spallation source facilities worldwide. With the advent of new and improved instrument design, detector methodology, source characteristics and data analysis protocols, these neutron scattering techniques are emerging as a primary tool for research to design, evaluate and implement advanced membrane technologies for fuel cell and separation devices. Here we describe these techniques and their development and implementation at the ILL reactor source (Institut Laue-Langevin, Grenoble, France) and ISIS Neutron and Muon Spallation source (Harwell Science and Technology Campus, UK) as examples. We also mention similar developments under way at other facilities worldwide, and describe approaches such as combining optical with neutron Raman scattering and x-ray absorption with neutron imaging and tomography, and carrying out such experiments in specialised fuel cells designed to mimic as closely possible actual operando conditions. These experiments and research projects will play a key role in enabling and testing new membrane formulations for efficient and sustainable energy production/conversion and separations technologies.